Temporal Relationship Between Juvenile Idiopathic Arthritis Disease Activity and Uveitis Disease Activity. Issue 3 (28th January 2022) - Liebling, Emily J.; Faig, Walter; Chang, Joyce C.; Mendoza, Elizabeth; Moore, Nicholas; Vicioso, Nahomy Ledesma; Lerman, Melissa A.
Abstract : Objective: To determine whether there is a temporal association between arthritis and uveitis activity among children with juvenile idiopathic arthritis–associated uveitis (JIA‐U). Methods: Uveitis and arthritis data from patients with JIA‐U age ≤21 years were collected from July 2013 to December 2019 at a tertiary care center. Arthritis activity was assessed at each rheumatology visit, and the primary outcome was the presence of active uveitis at ophthalmologic examination within 45 days of the rheumatology visit. Repeated‐measures logistic regression was used to evaluate the temporal association between any uveitis activity within 45 days of arthritis activity. Models were adjusted for demographic‐, disease‐, and treatment‐related factors. Results: A total of 98 patients were included: 81 (83%) female, 67 (69%) antinuclear antibody positive, 59 (60%) oligoarticular, and 13 (13%) enthesitis‐related arthritis (ERA) subtypes. There were 1, 229 rheumatology visits, with a median of 13 visits per patient (interquartile range 7–18). Concordance between arthritis and uveitis activity was observed 73% of the time (694 of 947). There was an independent temporal association between uveitis and arthritis activity (odds ratio 2.47 [95% confidence interval 1.72–3.54]; P < 0.01), adjusted for demographic and disease characteristics. Use of combination biologic and nonbiologic disease‐modifying antirheumatic drugs, female sex, HLA–B27 positivity, and ERA and polyarticular (rheumatoid factor negative) subtypes were associated with decreased odds of active uveitis at any time point. Conclusion: In patients with JIA‐U, there is a significant temporal association between arthritis and uveitis disease activity. These novel results suggest that an arthritis flare should prompt an expedited referral to the ophthalmologist.